Serotonin Reuptake Inhibitors and the Gut Microbiome: Significance of the Gut Microbiome in Relation to Mechanism of Action, Treatment Response, Side Effects, and Tachyphylaxis - Sjöstedt, Peter; Enander, Jesper; Isung, Josef (Frontiers in Psychiatry, 2021)
The monoamine hypothesis of psychopharmacology has been dominating the biological psychiatric research field for decades. Currently psychiatric research has increasingly appreciated psychiatric disorders and suicidal behavior as being highly complex and multi-etiological. In this pathway the gut microbiome and its interrelationship with the brain is gaining traction. The usage of selective serotonin reuptake inhibitors (SSRIs) is increasing in the general population. This is due to their effect on a broad range of psychiatric disorders, and their favorable side effect profile. Still, there are enigmatic aspects about SSRIs, such as the difficulty to predict effect in individual patients, inter-individual differences in side effect, tachyphylaxis (a sudden loss of response to a certain drug), and to date, uncertainties on how they exert their clinical effect. A majority of the serotonin in the human body is produced within the gut, and SSRIs affect enteric neurons. They also exhibit antimicrobial properties that comes with the potential of disrupting microbial hemostasis. We propose that the role of the gut-brain axis and the gut microbiome in relation to psychopharmacology should be more highlighted. With this article, together with similar articles, we would like to provide a hypothetical framework for future studies within this field. We believe that this would have the potential to provide a paradigm shift within the field of psychopharmacology, and result in findings that potentially could contribute to the development of a more personalized and tailored treatment.